Orchid Inventory along The Wongaya Gede Trekking Route of Mount Batukaru, Tabanan, Bali - Indonesia - Kania Delima Rizky; Ni Made Gari; I Made Saka Wijaya (Advances in Tropical Biodiversity and Environmental Sciences, 2026)
Orchids are among the most diverse groups of flowering plants, with a wide distribution. However, updated information on their distribution in Mount Batukaru, Bali, remains limited. The mountain was designated as a Cagar Alam (nature reserve) in 2020, highlighting the need for baseline data to support conservation efforts. This study aimed to document orchid species along the western slope through exploration surveys conducted from November 2024 to May 2025 across an elevation gradient from 831 to 2,276 m asl. Data were collected through direct field observations and photographic documentation, while species identification was verified using standard taxonomic references. A total of 25 species were recorded, representing two subfamilies, Epidendroideae (24 species) and Orchidoideae (one species, Corymborkis veratrifolia). Several species not reported in the previous study, including Arundina graminifolia, Calanthe zollingeri, Coelogyne speciosa, and Dendrobium spathilingue, were identified. Notably, Bulbophyllum ovalifolium corresponded to the MB2 (Mount Batukaru 2) variant previously reported from Mount Batukaru. The updated data can be used to evaluate the effectiveness of nature reserve designation and guide future conservation strategies.